Simulation of piezoelectric micro ultrasoniv transducer for underwater aplications - Siti Azizah Muhamad Lofti (Tanjong Malim, 2024)
Simulation of piezoelectric micro ultrasoniv transducer for underwater aplications by Siti Azizah Muhamad Lofti